If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(5 + -1f) = 75 (5 * 5 + -1f * 5) = 75 (25 + -5f) = 75 Solving 25 + -5f = 75 Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-25' to each side of the equation. 25 + -25 + -5f = 75 + -25 Combine like terms: 25 + -25 = 0 0 + -5f = 75 + -25 -5f = 75 + -25 Combine like terms: 75 + -25 = 50 -5f = 50 Divide each side by '-5'. f = -10 Simplifying f = -10
| 4x+12=-6x-18 | | (z-3-2i)(z+8i)=(z+3i)(z+2) | | 6/7=x/84 | | 0.60x+0.30(80)=0.30(146) | | -(15-3s)-(9s+5)=28 | | 3[2(3x+2)-4(2x-5)]-2(3x+1)=4(x+1)-2(3x+5) | | 11x-12=9x+5 | | 24x+8=432 | | 34=-4j | | 2y-3+5y=9 | | 3x+3=5*2x+1 | | 2k^3+9k^2+23k=288 | | 7(t-3)+32t=9(t+1) | | -214-(-87)=x | | 6=-5/w-5 | | -10n=20 | | 1/2x=x+10- | | x+(x-18)=150 | | 3(2y-6)=-9(y-8) | | 13x+1y=25 | | [-2x+4]=4 | | -3[2t+1]=9 | | -10=-4v-v | | 8x+1=10-5x | | 3/4[8t-12]=6(t-1) | | 2x-5x=y | | a+bi+6(a-bi)=7 | | 27rst+27tsr= | | 3/4[8t-12]=6(1-1) | | 13+-7-10x=2 | | -5b=25 | | 12*90= |